2004
DOI: 10.1002/jcb.20069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homocysteinylation of low density lipoproteins on lipid peroxidation of human endothelial cells

Abstract: Homocysteine-thiolactone (HcyT) is a toxic product whose synthesis is directly proportional to plasma homocysteine (Hcy) levels. Previous studies demonstrated that the interaction between HcyT and low density lipoproteins (LDL) induces the formation of homocystamide-LDL adducts (Hcy-LDL). Structural and functional alterations of Hcy-LDL have been described and it has been suggested that homocysteinylation could increase atherogenicity of LDL. Oxidative damage of endothelial cells (EC) is considered to be a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 38 publications
6
64
1
2
Order By: Relevance
“…At least 9 free sulfhydryl groups (ϪSH) in apoB-100 primary structure have been reported that could potentially bind plasma free aminothiols (13 ). Because lysyl residues of apoB could react in vivo with plasma HcyT by an amide bond, the number of these apoprotein sulfhydryl groups could increase considerably, thus increasing the number of sites that may be bound by plasma aminothiols (9 ). Even if we did not measure protein N-homocysteinylation concentrations, a 50 g/L LDL solution can be calculated to contain ϳ1 mol/L of Hcy-N-apoprotein, as recently reported by Jakubowski (29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 9 free sulfhydryl groups (ϪSH) in apoB-100 primary structure have been reported that could potentially bind plasma free aminothiols (13 ). Because lysyl residues of apoB could react in vivo with plasma HcyT by an amide bond, the number of these apoprotein sulfhydryl groups could increase considerably, thus increasing the number of sites that may be bound by plasma aminothiols (9 ). Even if we did not measure protein N-homocysteinylation concentrations, a 50 g/L LDL solution can be calculated to contain ϳ1 mol/L of Hcy-N-apoprotein, as recently reported by Jakubowski (29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even at low concentrations (up to 10 mol/ L), Hcy is cytotoxic and induces cell injury and oxidative damage in cultured cells, with generation of reactive oxidative species, formation of superoxide and hydrogen peroxide, and increased lipid peroxidation product concentrations (10,11 ). LDL incubation with 100 mol/L HcyT for 2 h was reported to cause the N-homocysteinylation of ϳ10% of apoB100 lysyl residues (9 ). Assuming a relative molecular mass (M r ) of ϳ500 000 for apoB and ϳ200 lysyl residues per apoB molecule (12 ), ϳ20 new ϪSH groups are introduced in the sequence of apoprotein, thus tripling the number of "free sulfydryl" groups of native protein, reported to be 9 (13 ).…”
mentioning
confidence: 99%
“…For example, homocysteinylated molecules gain biotoxic features like LDL molecules, which after interaction with HTL can induce endothelial lipid peroxidation (Ferretti et al 2004) or peroxynitrite production by human aortic endothelial cells (Ferretti et al 2006). Coagulation factor Va is also S-homocysteinylated (Undas et al 2001) and this modification could play a role in the modulation of hemostasis process.…”
mentioning
confidence: 99%
“…In an experimental model, it has been demonstrated that homocysteinylated LDL intensifies the cytotoxic effect associated with increased lipid peroxidation and oxidative vascular endothelial cell damage. 22,23 The vascular endothelium damaged by hyperhomocysteinemia initiates inflammation and development of atherosclerotic lesions. 24 In women, we observed an association between lower HDL-C and elevated Hcy levels, which might increase the probability of HDL modification by Hcy.…”
Section: Methodsmentioning
confidence: 99%